Enantiostylous types of Cassiinae species (Fabaceae‐Caesalpinioideae). (14th January 2015) - Almeida, N. M.; Cotarelli, V. M.; Souza, D. P.; Novo, R. R.; Siqueira Filho, J. A.; Oliveira, P. E.; Castro, C. C.; Dafni, A.
Abstract Species of the subtribe Cassiinae present a wide diversity of floral types. Until recently it was considered that this diversity did not extend to their reproductive mechanisms. However, studies have recorded some variations in the enantiostylous pattern in this plant group. This study aims to investigate the morphological and functional variations of enantiostyly in species of the subtribe Cassiinae. Additionally, it proposes the recognition of enantiostylous types (ET) based on pollen deposition and capture mode. Morphological data were collected in fresh and fixed (alcohol 70%) buds and flowers, and also using photos and rehydrated material from herbarium sheets, for a total of 59 species. The parameters used to establish the ETs were pollination type, nature of pollen deposition on the pollinator body, deposition type, number of petals involved in pollen deposition, and pollen pathway. Morpho‐functional features allowed the recognition of seven enantiostylous types (Flexuosa, Cana, Macranthera, Martiana, Amiciella, Repens and Ramosa) that present several levels of complexity. The type Ramosa was the most common and the Cana type was the least common. The types Repens, Martiana and Flexuosa do not have reciprocal pollen deposition, thus species with these types may be considered atypical. The groups resulting from similarity analysis partially coincide with the clades proposed in phylogenetic studies of Cassiinae. The recognition of functional ETs is important for understanding the evolution of reproductive strategies of Cassiinae species, and indicates an interesting line of investigation of enantiostyly in other plant groups.